+0

# [(2x+1)/3]+[(5x-2)/2]-[(3x-3)/5]=2

0
938
4

[(2x+1)/3]+[(5x-2)/2]-[(3x-3)/5]=2

Feb 8, 2016

#2
+15

Hi Rarinstraw,

This is the BEST way to do it :)

$$\frac{(2x+1)}{3}+\frac{(5x-2)}{2}-\frac{(3x-3)}{5}=2 \\ \mbox{Multiply through by the lowest common multiple - that is 30}\\ \frac{30(2x+1)}{3}+\frac{30(5x-2)}{2}-\frac{30(3x-3)}{5}=60 \\ \frac{10(2x+1)}{1}+\frac{15(5x-2)}{1}-\frac{6(3x-3)}{1}=60 \\ 10(2x+1)+15(5x-2)-6(3x-3)=60 \\ \mbox{See that got rid of all the fractions :)}\\ 20x+10+75x-30-18x+18=60\\ 20x+75x-18x+18+10-30=60\\ 77x-2=60\\ 77x=62\\ x=\frac{62}{77}\\$$

.
Feb 8, 2016

#1
+3

2/3x + 1/3 + 2 1/2x - 1 - 3/5x - 3/5 =2

Combine like terms.

The decimals are approximate, the numbers would have repeated for ages otherwise.

2.57x - 1.26 = 2

2.57x=3.26

2.57x=3.26 = x=(326/257)

Feb 8, 2016
#2
+15

Hi Rarinstraw,

This is the BEST way to do it :)

$$\frac{(2x+1)}{3}+\frac{(5x-2)}{2}-\frac{(3x-3)}{5}=2 \\ \mbox{Multiply through by the lowest common multiple - that is 30}\\ \frac{30(2x+1)}{3}+\frac{30(5x-2)}{2}-\frac{30(3x-3)}{5}=60 \\ \frac{10(2x+1)}{1}+\frac{15(5x-2)}{1}-\frac{6(3x-3)}{1}=60 \\ 10(2x+1)+15(5x-2)-6(3x-3)=60 \\ \mbox{See that got rid of all the fractions :)}\\ 20x+10+75x-30-18x+18=60\\ 20x+75x-18x+18+10-30=60\\ 77x-2=60\\ 77x=62\\ x=\frac{62}{77}\\$$

Melody Feb 8, 2016
#3
0

Looks a whole lot easier! Good job Melody!

rarinstraw1195  Feb 8, 2016
#4
0

Thanks rarinstraw :)

Feb 9, 2016